ANALISIS DAMPAK KURIKULUM CINTA DALAM PENDIDIKAN ISLAM SEBAGAI PENDIDIKAN TRANSFORMATIF YANG MENGUBAH PERSPEKTIF DAN SIKAP PESERTA DIDIK: KAJIAN PUSTAKA TEORITIS DAN PRAKTIS - Aslan, Aslan; Opan Arifudin (CV. Adiba Aisha Amira, 2025)
This study aims to analyse the impact of the love curriculum in Islamic education as a form of transformative education that can change the perspectives and attitudes of students. The love curriculum is seen as an educational approach that integrates the values of compassion, rahmatan lil 'alamin, and humanism into the learning process. The method used is a literature review with a descriptive-analytical approach, examining scientific literature related to the theoretical basis and practical application of the love curriculum in Islamic educational institutions. The results of the study show that, theoretically, the love curriculum functions as a philosophical and pedagogical foundation that unites the spiritual, moral, and social dimensions of Islamic education. In practical terms, this curriculum produces significant changes in the attitudes and perspectives of students, such as increased social empathy, inclusive attitudes, and cooperative behaviour. The love curriculum also contributes to creating a conducive learning climate and minimising negative behaviour. The findings of this study emphasise the urgency of developing the love curriculum as a transformative Islamic education innovation and recommend strengthening teacher training and support systems for its implementation.